Promoting Social Welfare and Development: the Role of NGOs in Himachal Pradesh. - Sharma, Vijay Kumar, Kumar, Anuj, Verma, L.R. and Sharma, Nisha (2011)
Society is a crucial component in the study of sociology as it is a holistic concept, a dynamic process and an important index of human development. There is a critical link between social and economic development. Society is considered as the core of development since good society leads to sustainable development thereby enhancing economic growth and increasing environmental sustainability. Good society of the nation facilitates social growth, social progress and social development. These can only be achieved if human development is made the key to integrated development by encompassing several inter-sectoral processes and opting for various goals and indicators. These goals are eradication of social evils, improving social status, women‟s empowerment, promotion and preservation of culture, encouraging SHGs, yuvak and yuvti mandals, etc. Thus, for holistic development of the society, there is a need to evolve and focus on growth or progress not just in terms of socio-economic growth but also by addressing all components and processes which enlarge people’s choice.